2022
DOI: 10.1002/cphc.202200132
|View full text |Cite
|
Sign up to set email alerts
|

Insights and Activation Energy Surface of the Dehydrogenation of C2HxO Species in Ethanol Oxidation Reaction on Ir(100)

Abstract: Dehydrogenation of an organic compound is the first and the most fundamental elementary reaction in many organic reactions. In ethanol oxidation reaction (EOR) to form CO 2 , there are a total of 46 pathways in C 2 H x O (x = 1-6) species leading to the removal of all six hydrogen atoms in five CÀ H bonds and one OÀ H bond. To investigate the degree of dehydrogenation in EOR under operando conditions, we performed density function theory (DFT) calculations to study 28 dehydrogenation steps of C 2 H x O on Ir(1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 106 publications
0
9
0
Order By: Relevance
“… a The unit of energies is in eV. b Full reaction species are listed in Table S1. H in product is omitted; b- and h- represent bridge-site and hollow-site adsorbed species. c Data for another type of transition state is shown in Table S4. d Data taken from ref . e Data taken from ref . f Data taken from ref . …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… a The unit of energies is in eV. b Full reaction species are listed in Table S1. H in product is omitted; b- and h- represent bridge-site and hollow-site adsorbed species. c Data for another type of transition state is shown in Table S4. d Data taken from ref . e Data taken from ref . f Data taken from ref . …”
Section: Resultsmentioning
confidence: 99%
“…Unlike the catalytic oxygen reduction, 10−12 there are 46 dehydrogenation reactions and 24 possible C−C bond cleavages of C 2 H x O species in anode catalysis. 13 These 70 reactions exclude the potential reactions of C−O or C−OH decoupling of C 2 H x O species. Furthermore, the EOR network has to include the less studied oxidations of C 1 species to form CO 2 as well as water dissociation, which are largely lacking studies, but will be demonstrated in this work as critical for the design of EOR catalysts.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Silver nanoparticle (AgNP) is one of the emerging and fastest growing materials in the field of nanotechnology [1][2][3] and Biomedicine [4][5][6][7][8] that benefited from the advancements in the studies of nanoparticles [9][10][11][12][13][14] and applications such as in catalysis [15][16][17][18][19][20][21][22][23][24][25][26][27][28] . The rapid growth of Agbased nanomaterials is attributed to silver's antimicrobial properties [29][30][31][32][33][34][35] , good optical, conductive, and other outstanding properties [36][37][38][39] .…”
Section: Introductionmentioning
confidence: 99%